2011
DOI: 10.1063/1.3590335
|View full text |Cite
|
Sign up to set email alerts
|

Activation of erbium films for hydrogen storage

Abstract: Hydriding of metals can be routinely performed at high temperature in a rich hydrogen atmosphere. Prior to the hydrogen loading process, a thermal activation procedure is required to promote facile hydrogen sorption into the metal. Despite the wide spread utilization of this activation procedure, little is known about the chemical and electronic changes that occur during activation and how this thermal pretreatment leads to increased rates of hydrogen uptake. This study utilized variable kinetic energy X-ray p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…The partial reduction of the oxide increases the surface reactivity and permeability of the oxide to hydrogen [12]. The formation of the UO x C y phase increases H 2 dissociation upon and subsequent transport through the oxide by improving conduction of electrons to the surface [13].…”
Section: Resultsmentioning
confidence: 99%
“…The partial reduction of the oxide increases the surface reactivity and permeability of the oxide to hydrogen [12]. The formation of the UO x C y phase increases H 2 dissociation upon and subsequent transport through the oxide by improving conduction of electrons to the surface [13].…”
Section: Resultsmentioning
confidence: 99%
“…An ''activation'' step is needed in order to get the H:Er reaction to happen [19]; however, the activation step is not associated with an energy barrier to the reaction that needs to be overcome. Instead, it has been shown that upon heating erbium films, oxygen is driven into the bulk of the erbium leaving an oxygen deficient Er 2 O 3Àx surface that reacts with and permits the diffusion of hydrogen [33,37]. Parish et al showed that oxygen is a very common contaminant in erbium films, forming dispersed erbium oxide nanoinclusions and larger macroscopic particles [24].…”
Section: Erbium Hydridementioning
confidence: 97%
“…If the air exposed erbium film is then hydrided, the oxide thickness increases, depending on the hydrogen gas purity [36]. While the oxide surface is predominantly Er 2 O 3 , the presence of hydroxides has also been detected using XPS [33,37]. Even though the heat of formation for ErH 2 is negative (À2.30 eV/mole) [34], the reaction does not proceed because the erbium oxide layer prevents hydrogen diffusion into the bulk and the H:Er reaction.…”
Section: Erbium Hydridementioning
confidence: 98%
“…This is in agreement with the observations of Swissa et al [11] and Brumbach el al. [7] who reported thermally driven redistributions of the oxygen from the oxide over-layer into the bulk metal for uranium and erbium respectively. Shown in Figure 4 are the O1s and C1s regions of XPS spectra obtained from as-polished and annealed samples.…”
Section: Surface Analysismentioning
confidence: 98%
“…Recently, vacuum annealing has been shown to promote the surface reactivity of some rare earth metals towards hydrogen adsorption owing to the desorption of surface contaminants and modifications to the oxide over-layer [5][6][7], therefore, a similar enhanced surface reactivity with uranium could be expected [8].…”
Section: Introductionmentioning
confidence: 99%